St. Cordula und die Kölner Johanniter. Zu Rolle und Funktion weiblicher Heiliger und ihrer Reliquien - Krämer, Thomas (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2023)
St. Cordula and the Cologne Johanniter. On the role and function of female saints and their relics The Hospitaller commandery in Cologne not only had an extraordinarily rich collection of relics, it was almost unique in having relics found on its own grounds. In 1278 and 1327, remains of several saints were collected, which were attributed to the entourage of St Ursula and the 11.000 virgins. These were not particularly high-ranking saints, but the Hospitallers knew how to cleverly use the findings to secure a prominent place for their house in the legend, which was very well known throughout Europe. With the relics, especially those of St Cordula, whose discovery was staged in a hagiographic text, the Hospitaller commandery also succeeded in placing itself in Cologneʼs very dense sacral landscape and establishing connections far beyond the city and the Rhineland. Especially in difficult situations, the finding of the relics offered members of the order and the social environment of the commandery’s self-assurance, as they confirmed the promise of salvation. Last but not least, pilgrims and donations brought economic benefits. This article demonstrates that a particularly high-ranking relic or saint was not necessarily needed to be successful. Falling back on those who fit into a narrative that offered different points of contact could be just as advantageous in securing support and gaining influence.